Peran Program Pemerintah Dalam Meningkatkan Kesejahteraan Masyarakat Pada Masa Pandemi Dalam Perspektif Ekonomi Islam - Ainulyaqin, MH; Sakum, Sakum; Edy, Sarwo (ITB AAS INDONESIA Surakarta, 2023)
This study aims to determine the role of government programs in improving people's welfare during the pandemic in the perspective of Islamic economics in the people who receive BLT, BPNT, and PKH assistance in Telukjaya Village. This research is a qualitative approach with a field research. The data collection techniques were carried out by observation, interviews, and documentation. While the object of research is the community who received BLT, BPNT and PKH assistance during the pandemic as well as several Telukjaya Village staff. The results of this study, already from the results of interviews regarding the role of the Government's BLT, BPNT, & PKH assistance programs are correct. Measured using four indicators, namely: Accuracy of targets, program socialization, program objectives, and program understanding, it shows that almost all indicators are appropriate, except that program socialization has not been maximized due to regulatory constraints during the pandemic. In Sharia, it can be said that the government has implemented the principles of responsibility, justice, defense and security.